TERAPI OKSIGEN HIPERBARIK SEBAGAI TERAPI TAMBAHAN UNTUK LUKA KAKI DIABET - Chilyatiz Zahroh (Jurnal Ilmiah Kesehatan, 2013)
Gangrenous wounds is one of the chronic complications of diabetes that most feared by every diabetic patient (Tjokroprawiro, 2007). Gangrenous wounds is a condition that begins from the tissue hypoxia where oxygen is reduced, it will affect the activity of vascular and cellular networks, which results in tissue damage (Guyton, 2006). TOHB (Hyperbaric Oxygen Therapy) or Hyperbaric Oxygen Therapy or HBO therapy (Hyperbaric Oxygen) is a way to increase tissue oxygen levels, by reducing the swelling caused by vasoconstriction of blood vessels. At the same time, TOHB also increases oxygen levels in the blood (Neubauer, 1998). Oxygen is expected to penetrate through to the peripheral tissues are deprived of oxygen, so that the supply of nutrients and oxygen are met, so that the network can do metabolism and function (Smeltzer, 2002). Review was conducted at 10 research/article. Search strategy articles by using two ways: manual and online libraries. This search is getting 113 articles, but the total articles reviewed were the 10 articles. 1 studies are case reports and 9 research is experimental research with 5 studies using random techniques. TOHB with adequate doses can have a positive effect on wound healing and reduce the risk of amputation. TOHB beneficial to improve peripheral perfusion and decrease the incidence of major amputation. However, there has been no research on the psychology of the patient.